Conscientious objection and reproductive health in Chile: two paradigmatic cases - Casas Becerra, Lidia; Dides Castillo, Claudia (Acta Bioethica, 2007)
This paper meditates upon conscientious objection and reproductive health in two paradigmatic cases: emergency contraception and voluntary sterilization. Several questions arise regarding conscientious objection towards reproductive health and its ethical (and political) dilemma. As a democratic society we should be concerned about both of them..